A chromosome-level genome assembly of the Chinese cork oak (Quercus variabilis) - Han, Biao; Wang, Longxin; Xian, Yang; Xie, Xiao-Man; Li, Wen-Qing; Zhao, Ye; Zhang, Ren-Gang; Qin, Xiaochun; Li, De-Zhu; Jia, Kai-Hua (Frontiers in Plant Science, 2022)
Quercus variabilis, a member of the Fagaceae family, is an ecologically and economically important deciduous broadleaved tree species native to and widespread in East Asia. It is regarded as a precious woody species and a local forest health indicator, occupying a dominant position in forest ecosystems in East Asia. However, genomic resources of Q. variabilis are still lacking. We present a high-quality Q. variabilis genome by PacBio HiFi and Hi-C sequencing. The assembled genome size was 787 Mb, with a contig N50 of 26.04 Mb and scaffold N50 of 64.86 Mb, comprising 12 pseudo-chromosomes. The repetitive sequences constituted 67.6% of the genome, among which long terminal repeats (LTRs) were the majority type of repetition, accounting for 46.62% of the genome. Ab initio, homology-based and RNA sequence-based gene prediction identified 57,873 protein-coding genes, of which 93.25% of the total genes could be functionally annotated. Evolutionary analysis showed that Q. variabilis was more closely related to Q. suber than to Q. lobata and Q. robur, and no evidence for species-specific whole genome duplication (WGD) in Quercus. This study provides the first genome assembly and gene annotation for Q. variabilis. The availability of these resources will be of great importance for further breeding strategies, genome editing, and comparative genomics among oak species.